EP905 Ovarian cancer treatment in the elderly. (1st November 2019) - Kaparelou, M; Tsiara, A; Zakopoulou, R; Kyriazoglou, A; Cohen, A; Liontos, M; Tsironis, G; Koutsoukos, K; Theofanakis, C; Thomakos, N; Zagouri, F; Haidopoulos, D; et al.
Abstract : Introduction/Background: Treatment of elderly patients with neoplasia is challenging due to the frailty of the patients, existing comorbidities and increased number of concomitant medications. In addition, elderly patients are usually underrepresented in clinical trials. Age is a known prognostic factor in ovarian cancer but optimal treatment of elderly patients has not been determined. We undertook a retrospective analysis to determine clinical practice in advanced stage ovarian cancer patients older than 75 years of age. Methodology: Medical records of women with high grade serous and endometrial ovarian cancer, stage III and IV, treated at Alexandra Hospital from 2011 to 2016 were retrospectively identified. Clinicopathological data, treatment and survival data were analyzed. Kaplan-Meier Survival curves were generated using IBM SPSS version 20; survival differences were estimated using the long-rank test. Results: In total, 158 patients were identified with a median age of 61.1 years. Among them 20 (12.7%) were older than 75 years of age at diagnosis (range 75.03–92.72 years). First line Progression Free Survival (PFS) and Overall Survival (OS) were statistically significant worse in elderly patients in comparison to the younger ones (mPFS 13.4 months vs 21.9 months, P<0.001 and mOS 25.3 months vs 51, 5 months, P<0.001). However, elderly patients were characterized by worse ECOG-PS, more frequent treatment with Neoadjuvant Chemotherapy followed by Interval Debulking Surgery, more frequently denied debulking surgery, and received monotherapy with platinum as frontline treatment, while were less frequently tested for BRCA mutations. In contrast, there was no statistical significant difference in the outcome of the debullking surgery in comparison to the younger patients. Age over 75 years retained its statistical significance for OS when adjusted for all other reported prognostic factors. Conclusion: Elderly ovarian cancer patients have worse prognosis independent of treatment. Comprehensive geriatric assessment should be performed for the optimal treatment of these patients. Disclosure: Nothing to disclose.